The methodology of calculation of sample size in "non-inferiority" comparative controlled clinical trials: a comparison of two proportions in parallel group - A. A. Lyashenko; M. S. Svishcheva (Izdatelstvo OKI, 2018)
The absolute majority of clinical trials of generic drugs aimed to compare the therapeutic efficacy of the tested drug and the drug of an active control. It is necessary to estimate that the test drug is not less effective (or non-inferior) than the control drug. The designs of the aforementioned trials are called "non-inferiority" study; often, these are phase III of clinical trials. The primary criterions of effectiveness which are quite often used in the clinical trials are frequencies of signs, as a result of the analysis of binary data. Binary data are analyzed by comparing proportions. One of the most important conditions for a correct interpretation of the data obtained during the clinical trials - to provide necessary and suffi cient sample size. The purpose of this article is to show how to plan the study, how to provide necessary and sufficient sample size to ensure that the results and conclusions would be reliable; how to interpret the data in a comparative controlled study aimed to establish "noninferiority" using proportions comparing in parallel groups.